Boots beneath her bed - Esposito, Taylor (Romance fiction writer) (Berkley Romance, 2026)
"A mysterious horse trainer with a dark past ropes the heart of a guarded ranch foreman in this steamy cowboy romance by debut author Taylor Esposito. Grace Underwood has been hiding a dark secret about the day her parents died. Only her ruthless uncle Bellamy knows the truth, and he's been using it against her ever since. When his cruelty finally goes too far, she risks everything to walk away, with no plan and nowhere to turn. Then a chance opportunity falls into her lap: a job as a horse trainer at Halcyon Ranch, one of the largest ranches in the country. It's more than she ever expected, and for the first time, she begins to imagine a future of her own making. But settling in isn't easy. Crew Caldwell - the owner's son and Halcyon's foreman - makes it clear he doesn't trust outsiders, least of all someone from Bellamy Whitlock's bloodline. Though Grace's determination and undeniable gift with horses slowly begin to win over the other ranch hands and even the Caldwell family itself, Crew remains the hardest to reach, the one man she shouldn't want but can't seem to ignore. As the tension between them grows, so does the risk of Grace's secret unraveling. And with unfinished business with her uncle still looming, she'll have to decide whether she's willing to fight for the only place - and the only man - that's ever felt like home"-- Provided by publisher.